2016
DOI: 10.21009/insight.041.17
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Dukungan Sosial Dan Motivasi Berprestasi Siswa Kelas Vii Di Madrasah Tsanawiyah Negeri 8 Jakarta Barat

Abstract: AbstrakPenelitian survey yang bersifat korelasional ini bertujuan untuk bertujuan untuk mengetahui gambaran dukungan sosial dan motivasi berprestasi siswa dan mengetahui ada hubungan positif dan signifikan antara dukungan sosial dan motivasi berprestasi siswa kelas VII di Madrasah Tsanawiyah Negeri 8 Jakarta Barat. Penelitian ini dilakukan pada bulan Januari-November 2014. Populasi penelitian ini adalah 210 siswa. Teknik sampling yang digunakan dalam penelitian ini adalah Propotional Random Sampling dengan jum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
2
0
0
2
Order By: Relevance
“…Raden Rahmat Islamic University, Malang. This conclusion was supported by the results of the previous study conducted by Kusuma, et. al.…”
Section: Resultssupporting
confidence: 87%
“…Raden Rahmat Islamic University, Malang. This conclusion was supported by the results of the previous study conducted by Kusuma, et. al.…”
Section: Resultssupporting
confidence: 87%
“…For instance, a study conducted on 380 vocational school students in Bandung revealed that a majority of the students had not yet reached a level of career maturity and lacked clarity about their future prospects (Prahesti, 2018). Similarly, other research has indicated that vocational students generally have a low level of career maturity, which is characterized by a lack of career planning and access to relevant information (Kusuma et al, 2015). This aligns with findings that female students tend to exhibit higher career maturity levels compared to their male counterparts, and vocational students tend to have higher career maturity levels compared to high school students (Marpaung et al, 2016).…”
Section: Introductionsupporting
confidence: 56%
“…Hubungan dukungan sosial dengan motivasi belajar juga positif dan searah, artinya semakin tinggi dukungan sosial maka semakin tinggi juga motivasi belajar, yang pada akhirnya prestasi dari siswa SMA Negeri Bali Mandara yang terus meningkat. Selain itu juga, hasil penelitian dari Kusuma, Tjalla, & Setyowati (2015) menunjukkan bahwa Siswa kelas VII di Madrasah Tsanawiyah Negeri 8 Jakarta yang dikategorisasikan memiliki dukungan sosial tinggi sebanyak 13% dan motivasi berprestasi siswa tinggi sebanyak 17%, siswa yang dikategorisasikan memiliki dukungan sosial sedang sebanyak 47% dan motivasi berprestasi siswa sedang sebanyak 36%, siswa yang dikategorisasikan memiliki dukungan sosial rendah sebanyak 40% dan motivasi berprestasi siswa rendah sebanyak 47%.…”
Section: Pendahuluanunclassified